(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
Legal consciousness represents an essential component of professional and civic identity in both English and Uzbek speaking societies. This article explores the methods of forming legal consciousness and the pedagogical approaches used in the English and Uzbek educational systems from a comparative perspective. The study aims to identify the principal pedagogical strategies, including case-based learning, interactive seminars, and linguistic-legal integration, as well as to examine their historical development and cultural adaptation. The research is based on a comparative analysis of educational curricula and professional legal texts. The findings indicate that English pedagogical approaches are largely formed through a focus on common law precedents and critical analysis, whereas Uzbek pedagogical methods reflect a transition from traditional lecture-based systems to modern, interactive models incorporating national legal traditions. The study reveals both universal and language-specific features in the development of legal consciousness and underlines the significance of pedagogical innovation in ensuring professional competence. The results may be useful for further research in legal linguistics, comparative pedagogy, and English for Specific Purposes (ESP).